The neurology behind three wounded French artists during the great world war - VITTURI, Bruno Kusznir; SANVITO, Wilson Luiz (Arquivos de Neuro-Psiquiatria, 2020)
A unique association joins Guillaume Apollinaire, Blaise Cendrars and Louis Ferdinand Céline. Besides being great exponents of French literature, they were all neurologically wounded during the First World War. Apollinaire had a traumatic brain injury, Cendrars developed phantom limb neuropathic pain and Céline presented radial nerve paralysis. There is quite an evidence that supports that their artistic output was also influenced by acquired neurological conditions during the war. The examples of these three French authors reveal the surprising intimacy Neurology can share with art and history.
Keywords: art; history of neurology; traumatic brain injury; World War I; peripheral neuropathy